Dynamic Mechanical Analysis and Thermal Stability of Neem Wood Veneer Plastic Composites. (2020) - Nagamadhu, M.; Vijay Kumar, S.; Ravi Kumar, S.; Suraj, R.; Mohan Kumar, G.C.
Abstract: The neem wood veneer is used as core materials in many of the wood structural applications. In this research work, neem wood polymer composite (NWPC) were prepared to understand the effect of weight fraction, stacking sequence, and interfacial bonding between neem wood veneer and epoxy material. NWPC were prepared conventional compression molding and Thermo-mechanical properties of wood epoxy composite samples were investigated by the dynamic mechanical analyzer over the temperature range from 30 to 180°C. Storage modulus (G') and Loss modulus (G") of NWPC samples exhibited significant effect with respect weight fraction of wood veneer. Similarly epoxy has good interfacial bonding agent to enhance the strength of multilayered wood polymer composites. However, the stacking sequence having major changes in dynamic mechanical properties, G' & G" increases along the wood fiber direction with negligible load bearing capacity in transfers direction. By changing the orientation of the wood veneer properties improved in both the direction. Additionally, scanning electron microscopy (SEM) evidently shows the interfacial bonding efficiency